If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(5 + -1y) = 20 (5 * -4 + -1y * -4) = 20 (-20 + 4y) = 20 Solving -20 + 4y = 20 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '20' to each side of the equation. -20 + 20 + 4y = 20 + 20 Combine like terms: -20 + 20 = 0 0 + 4y = 20 + 20 4y = 20 + 20 Combine like terms: 20 + 20 = 40 4y = 40 Divide each side by '4'. y = 10 Simplifying y = 10
| 14(5-y)=20 | | x^2(5x-1/4)(2x+1/4) | | 1.7q-1.6-5.9q=5.2q-4.1 | | -3(2x-6)-4x+9= | | 7y+1=8y+5 | | x^2-x+64=0 | | 6x^2+12x+c=0 | | 8x+17=5x+35 | | x^2+4x+48=0 | | 8/x-5x=4 | | 5x^2-78=48 | | a=10ln(a) | | x-1-(x-2)(x+2)=9 | | 7.5m+1.1-10m=4.3-2.5m-3.2+1.7 | | 2x-8x+29=5 | | -3(-2)+y=-5 | | 6y/z | | -39-20+y=-5 | | -13-4x=-21 | | 2*(x+3)=a | | -20x^2+12x+27=0 | | 2x(x+3)=a | | 0=6x^2+6 | | 5(x-1)-2(x^2+5x+6)-7(x+6)= | | x+3/10=-3/10 | | 6x(x-2)=11 | | -6+4x=34 | | -7b+4=39 | | 7-4m=51 | | 8x-2+3x+4= | | 14-y=18 | | -12+5x=-2 |